A Flexible, Highly Accurate, and Stable Pressure Sensor with Anti‐Interference from Temperature, Sweat, and Humidity. Issue 6 (1st December 2022) - Ma, Jun; Liu, Qi; Yang, Liyan; Li, Mufang; Liu, Qiongzhen; Zhong, Weibing; Lu, Ying; Wang, Yuedan; Liu, Xue; Wang, Dong
Abstract: The highly accurate and stable pressure sensors with anti‐interference from varying sensing environments (temperature and humidity) are essential and a challenge in practical applications. However, real‐time electrical resistance fluctuation or even sensing inaccuracy are widely existed due to the sensibility of conductive materials towards varying temperatures, humidity, and sweat circumstance. Here, for the first time, the hydrophobic, non‐fluoride, titanium dioxide nanoparticle (TiO2 ‐ODI) modified carbon nanotube (CNT)/carbon black (CB) pressure sensors are introduced to achieve anti‐interference from temperature, droplets, and humidity. The sensors with a near‐zero temperature coefficient of resistance (near‐ZTC) effect (≈ −10 to 70 °C). The anti‐interference from moisture benefits from the effective isolation effect of the hydrophobic TiO2 ‐ODI layer. Meanwhile, the TiO2 ‐ODI/CNT/CB pressure sensors obtain a favorable sensitivity of 1.57 kPa −1, a fast response time of 20 ms, a negligible hysteresis ratio of 1.9%, prominent air permeability, and a facile scalable strategy. Hence, the TiO2 ‐ODI/CNT/CB pressure sensors are feasible for accurately and stably sensing under varying sensing environments by efficiently suppressing interferences from varying temperatures, high humidity, and sweat. Abstract : The flexible TiO2 ‐ODI/CNT/CB pressure sensors with prominent anti‐interference from temperature, sweat, and humidity simultaneously are first introduced to realize accurate and stable sensing. The sensors with a near‐ZTC effect (≈ −10 to 70 °C) and prominent hydrophobicity possess a sensitivity of 1.57kPa −1, a fast response time (20 ms), negligible hysteresis ratio (1.9%), good air permeability, and facile scalable strategy.